Respon Genotipe Jagung Tahan Kemasaman terhadap Pemberian Pupik N,P,K di Lahan Gambut - Hidayat Hidayat; Barnabas Ravirki; Darussalam Darussalam (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2026)
Maize (Zea mays L.) is one of the main staple food crops in Indonesia after rice, with great potential for cultivation across various land types, including peatlands. However, peat soils pose significant challenges due to their low pH and limited availability of essential nutrients such as nitrogen (N), phosphorus (P), and potassium (K). This study aimed to evaluate the response of acid-tolerant F15 maize genotypes to different NPK (15:15:15) fertilizer doses on peat soil. The experiment was conducted in Rasau Jaya II, Kubu Raya Regency, over five months (September 12, 2024 – January 12, 2025) using a Split Plot Design. The main plots consisted of five F15 maize genotypes (F15-1-Bm-2-3-Az-1, F15-1-Cm-2-3-Az-1, F15-1-Dm-2-3-Az-1, F15-I1-R3-B-3-AM-1, and F15-J1-R3-B-2-AZ-1), and the subplots included two NPK fertilizer doses: 400 kg/ha and 500 kg/ha. Observed variables included plant height, number of leaves below the ear, days to tasseling, days to silking, physiological maturity, ear weight with and without husk, ear length, ear diameter, number of kernel rows per ear, dry grain weight per ear, and 1000-grain weight. Results showed that most variables were not significantly affected by the treatments, except for the number of leaves above the ear, which was significantly influenced by genotype. The 400 kg/ha NPK dose was found to be the most efficient for supporting the growth and yield of F15 maize on peat soil.